2015
DOI: 10.1021/acs.jnatprod.5b00337
|View full text |Cite
|
Sign up to set email alerts
|

Transferring Fungi to a Deuterium-Enriched Medium Results in Assorted, Conditional Changes in Secondary Metabolite Production

Abstract: Deuterium is one of the few stable isotopes that have the capacity to significantly alter a compound's chemical and biological properties. The addition of a single neutron to a protium atom results in the near doubling of its mass, which gives rise to deuterium's characteristic isotope effects. Since the incorporation of deuterium into organic substrates is known to alter enzyme/protein-substrate interactions, we tested the extent to which deuterium enrichment would modify fungal secondary metabolite productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…As shown in Fig. 1 , 9 compounds were isolated from the ethyl acetate extract of strain E303035 and identified as cyclo(L-Leu-L-Pro) ( 1 ) (Yue et al 2010 ), cyclo(L-Pro-L-Tyr) ( 2 ) (Li et al 2013 ), Brevianamide F ( 3 ) (Wang et al 2015 ), 2-(3-Indolyl) ethanol ( 4 ) (Böhlendorf et al 1996 ), N-[2-(1H-indol-3-yl) ethyl] acetamide ( 5 ) (Anouhe et al 2015 ), 3, 3-di(1H-indol-3-yl)propane- 1,2-diol ( 6 ) (Zhao et al 2009 ), Lincomycin B ( 7 ) (Argoudelis et al 1965 ), dibutylphthalate ( 8 ) (Dai et al 2006 ), and p -hydroxyphenethyl alcohol ( 9 ) (Lou et al 2001 ).
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Fig. 1 , 9 compounds were isolated from the ethyl acetate extract of strain E303035 and identified as cyclo(L-Leu-L-Pro) ( 1 ) (Yue et al 2010 ), cyclo(L-Pro-L-Tyr) ( 2 ) (Li et al 2013 ), Brevianamide F ( 3 ) (Wang et al 2015 ), 2-(3-Indolyl) ethanol ( 4 ) (Böhlendorf et al 1996 ), N-[2-(1H-indol-3-yl) ethyl] acetamide ( 5 ) (Anouhe et al 2015 ), 3, 3-di(1H-indol-3-yl)propane- 1,2-diol ( 6 ) (Zhao et al 2009 ), Lincomycin B ( 7 ) (Argoudelis et al 1965 ), dibutylphthalate ( 8 ) (Dai et al 2006 ), and p -hydroxyphenethyl alcohol ( 9 ) (Lou et al 2001 ).
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…A fungus Aspergillus sp. from Waikiki Beach (Honolulu, HI), generated six isotopically labeled metabolites ( 3 – 8 ) when grown on the deuterium-enriched Czapek broth (Wang et al, 2015a), whereas this strain was found to metabolite a novel prenylated indole alkaloid, waikialoid A ( 9 ) when cultivated in PDB medium. Bioassay results indicated that compound 9 possessed potent inhibitory effect on biofilm formation of Candida albicans with an IC 50 value of 1.4 μM (Wang Q.X.…”
Section: Variation Of Mediummentioning
confidence: 99%
“…The organic extract was subjected to vacuum liquid chromatography (VLC) eluting with different solvents of increasing polarity from petroleum ether (PE) to MeOH to yield 9 fractions (Fr. [1][2][3][4][5][6][7][8][9].…”
Section: Extraction and Isolationmentioning
confidence: 99%
“…In our previous research, we obtained antimicrobial meroterpenoids from P. chermesinum EN-480 [4], and we recently tried to change the fermentation process to obtain more antibacterial secondary metabolites. As a result, we isolated three new sesquiterpenoids (1-3) as well as four known alkaloids, brevianmide F (4) [8], N-acetyltryptamine (5) [9], cyclo Trp-Ile (6) [10], and cyclo Ile-Pro (7) [11] (Figure 1). Compounds 1-3 were formed by esterification and cyclizing of catenulate farnesyl probably, and this is the first time this type of sesquiterpenoid from natural products has been described.…”
Section: Introductionmentioning
confidence: 99%